PEDAGOGICAL OPPORTUNITIES OF TEACHING LANDSCAPE COMPOSITION USING AR AND VR TECHNOLOGIES - Murodova Shohinabonu Alisher qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the pedagogical potential of using Augmented Reality (AR) and Virtual Reality (VR) technologies in teaching landscape composition. The study examines how immersive digital environments enhance students’ understanding of perspective, spatial arrangement, and color harmony. Findings indicate that AR and VR applications increase student engagement, facilitate interactive learning, and improve both technical and creative skills in visual arts education.